A construção crítica do núcleo de direitos humanos em face do princípio da prevalência dos direitos humanos - Galvão, Vivianny Kelly (2015)
The universalism vs. relativism dichotomy should not be perceived as a mere doctrinal issue. It means major obstacle to the effective protection of the human being in the international and internal orders. On one hand, the universal abstraction of human rights suffers severe critical, on the other hand, culture is dangerously positioned as an immutable element. It important to overcome this scenario and build the perception of common human rights. Even against this environment of disintegration, that rise of culture as an argument cannot put aside the protection of human life. The solution to the criticism of universalism and for strengthening the discourse of human rights relativism is the construction of a common core of human rights based on the prevalence of human rights. This research shows that it is so. Common is the space in which one of us are or wish to be part of. In the space of human rights, the common core was built by the main treaties of international law that form the so-called protection systems of the human being. It is very high level, because it goes beyond state borders. It was seat as essential assumptions the differential nature of the norms of international human rights law to ensure the international legal personality of the human person, beyond that, establishes the supremacy of international law over national law. Also, the foundation of the creation of the common core of human rights is in the primacy of human rights, defended as part of the ius cogens norm. The basis of the concept of common is the concept of policy in Hanna Arendt’s works. Therefore, the analysis of political activity in constructing common human rights toke place in international and domestic spaces. In international jurisdiction, the courts of human rights represent advances in constructing the hard core of human rights, although some structural aspects still deserve strong critics. In the Brazilian internal order, chaos around these matters is the main conclusion. Qualitative and quantitative methodologies were applied and, especially, the inductive, deductive, hypothetical-deductive methods of approach and typological method of procedure.